The effect of varied combinations of fermentation time on the quality of fermented (Peda) mackerel (Rastrelliger sp.) - Leksono, Tjipto; Sari, N. Ira; Rahayu, Rinaldi Fitra (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aimed to determine the effect of the combination of fermentation time at each fermentation stage on the quality of fermented “peda” mackerel (Rastreliger sp.) and to determine the optimal treatment combination of fermentation time to produce the best quality of “peda” mackerel. The research method used was an experiment by using a Completely Randomized Design (CRD) with 4 variants of combination treatments between the first stage fermentation time (A) and the second stage fermentation time (B), namely: 5 days and 4 days (A5B4), 5 days and 6 days (A5B6), 7 days and 4 days (A7B4), and 7 days and 6 days (A7B6). The results showed that the treatment of the fermentation time for 7 days at the first stage followed by the fermentation for 6 days at the second stage (A7B6) produced the best quality of “peda” mackerel and was significantly different from other treatments. The characteristics of “peda” mackerel produced were showing an attractive appearance, reddish brown in color; typical aroma of “peda” fish; delicious salty taste typical of fermented fish; and a semi-wet, flexible, and dense texture. The total content of lactic acid bacterias (LABs) in the fermented fish was 2.2 x 106 CFU/g; pH value 6.16; and aw value 0.65. Keywords: Fermentation Stage; Fermentation Time; Labs; Mackerel; Peda